Men of the West (Sheares St. Cork . 1915) (1916)
32 men.
Title inscribed in pen on verso, with the name of 6 of the men.
Keywords: O’Connell, J. J., -- 1888-1944; Irish Volunteers; Ireland -- History -- 1910-1921; Photographic prints -- Irish -- 1910-1920